2012
DOI: 10.1007/s10384-012-0133-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of visual field defects in pre-perimetric glaucoma using fundus-oriented small-target perimetry

Abstract: Fundus-oriented small-target perimetry is useful in detecting visual field abnormalities in PPG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Some studies have suggested that these eyes have glaucomatous optic disc abnormalities with localized RNFL damage in the fundus picture but without abnormal VF results. 16 However, this definition is highly subjective and dependent on examiner experience. Thus, Jampel et al 17 found that the interobserver agreement among glaucoma specialists in judging progressive optic disc changes from stereophotographs was slight to fair.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that these eyes have glaucomatous optic disc abnormalities with localized RNFL damage in the fundus picture but without abnormal VF results. 16 However, this definition is highly subjective and dependent on examiner experience. Thus, Jampel et al 17 found that the interobserver agreement among glaucoma specialists in judging progressive optic disc changes from stereophotographs was slight to fair.…”
Section: Discussionmentioning
confidence: 99%
“…14,17,18 It was recognized that the long test duration of SAPRO was a major limitation of this procedure, where 236 presentations were required to examine a 158 field with a 3.28 grid. 14 More recently, scotoma-oriented perimetry (SCOPE) 5,11 and fundus-oriented perimetry (FOP) 4,16,19,20 have been reported, which involve a clinician selecting more points to test within a region of interest. A procedure that automatically adds a fixed number of locations for further testing to a completed 24-2 pattern by computing the gradient between previously tested locations has also been proposed recently (Aoyama K, et al IOVS 2013;54:ARVO Abstract 3914).…”
mentioning
confidence: 99%